Respuesta :
Question 6
We want to find the equation of a circle with center (3,2) and radius 6.
The standard equation of a circle is given by:
[tex] {(x - a)}^{2} + {(y - b)}^{2} = {r}^{2} [/tex]
where (a,b) is the center of the circle and r is the radius.
We substitute (a=3,b=2) and r=6 to get;
[tex]( {x - 3)}^{2} + ( {y - 2)}^{2} = {6}^{2} [/tex]
Simplify:
[tex] {(x - 3)}^{2} + {(y - 2)}^{2} = 36[/tex]
Question 7
This time the center is (a=-4,b=-7) and radius is r= 8.
We substitute into the formula:
[tex] {(x - a)}^{2} + {(y - b)}^{2} = {r}^{2} [/tex]
To obtain:
[tex] {(x - - 4)}^{2} + {(y - - 7)}^{2} = {8}^{2} [/tex]
We simplify to get;
[tex] {(x + 4)}^{2} + {(y + 7)}^{2} = 64[/tex]
Question 8
Now the center is (a=5,b=-9) radius is r=10
We substitute
[tex] {(x - a)}^{2} + {(y - b)}^{2} = {r}^{2} [/tex]
To obtain;
[tex] {(x - 5)}^{2} + {(y - - 9)}^{2} = {10}^{2} [/tex]
We simplify to get:
[tex] {(x - 5)}^{2} + {(y + 9)}^{2} =100[/tex]
Question 9
This circle has center (-8,0) diameter 14.
To find the radius, we divide the diameter into 2.
[tex]r = \frac{14}{2} = 7[/tex]
We substitute the center and radius into the standard equation of the circle
[tex]{(x - a)}^{2} + {(y - b)}^{2} = {r}^{2} [/tex]
We simplify to obtain;
[tex]{(x - - 8)}^{2} + {(y - 0)}^{2} = {7}^{2} [/tex]
Simplify to get:
[tex]{(x + 8)}^{2} + {y }^{2} = 49[/tex]
Question 10.
This time we were given: center (4,5) and point on the circle (3,-7).
We determine the radius using the distance formula:
[tex]r = \sqrt{(x_2-x_1)^2 +(y_2-y_1)^2} [/tex]
We substitute the points to get:
[tex]r = \sqrt{(3-4)^2 +( - 7 - 5)^2} [/tex]
[tex]r = \sqrt{( - 1)^2 +( - 12)^2} [/tex]
[tex]r = \sqrt{1 +144} \\ r = \sqrt{145} [/tex]
We substitute the center (4,5) and radius in to the standard equation
[tex]{(x - a)}^{2} + {(y - b)}^{2} = {r}^{2} [/tex]
This gives us
[tex]{(x - 4)}^{2} + {(y - 5)}^{2} = { (\sqrt{145} })^{2} [/tex]
Simplify:
[tex]{(x - 4)}^{2} + {(y - 5)}^{2} = 145[/tex]
Question 11.
This time we have diameter with endpoints (6,4) and (10,-8).
The midpoint is the center of the circle.
By the midpoint rule, the center is ;
[tex]( \frac{10 + 6}{2} , \frac{4 + - 8}{2} ) \\ ( \frac{1 6}{2} , \frac{ - 4}{2} ) \\ ( \frac{10 + 6}{2} , \frac{4 + - 8}{2} ) \\ ( 8 , - 2)[/tex]
We find the radius using the distance formula:
[tex]r = \sqrt{(x_2-x_1)^2 +(y_2-y_1)^2} [/tex]
Substitute the center (8,-2) and the point (6,4).
[tex]r = \sqrt{(6 - 8)^2 +(4- - 2)^2} [/tex]
[tex]r = \sqrt{( - 2)^2 +(6)^2} \\ r = \sqrt{4+36} \\ r = \sqrt{40} [/tex]
We substitute the center and radius into the standard equation now to get;
[tex] {(x - 8)}^{2} + {(y - - 2)}^{2} = {( \sqrt{40} })^{2} [/tex]
Simplify;
[tex] {(x - 8)}^{2} + {(y + 2)}^{2} =40[/tex]
Question 12;
We were given center (4,9) and the condition that the tangent to this circle is the x-axis.
This means the radius is 9, the distance from the x-axis to the center.
We substitute the center (4,9) and radius r=9 into;
[tex] {(x - a)}^{2} + {(y - b)}^{2} = {r}^{2} [/tex]
to obtain:
[tex] {(x - 4)}^{2} + {(y - 9)}^{2} = {9}^{2} [/tex]
The required equation is
[tex]{(x - 4)}^{2} + {(y - 9)}^{2} = 81[/tex]